2009
DOI: 10.3325/cmj.2009.50.286
|View full text |Cite
|
Sign up to set email alerts
|

Kinship and Y-Chromosome Analysis of 7th Century Human Remains: Novel DNA Extraction and Typing Procedure for Ancient Material

Abstract: Application of forensic genetics in archaeology enables retrieving new types of information and helps in data interpretation. The number of successfully typed autosomal and Y-STR loci from ancient specimens in this study is one of the largest published so far for aged samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 22 publications
0
37
0
3
Order By: Relevance
“…Few ancient data are currently available on Y-haplogroups to confirm this hypothesis, but G2a haplotypes have been found in other prehistoric remains; two ancient DNA studies revealed the presence of G2a in the Czech Republic during the seventh century (31) and in a German sample of a central European Neolithic culture (13), whereas this haplogroup is very rare in these places nowadays (32).…”
Section: Resultsmentioning
confidence: 99%
“…Few ancient data are currently available on Y-haplogroups to confirm this hypothesis, but G2a haplotypes have been found in other prehistoric remains; two ancient DNA studies revealed the presence of G2a in the Czech Republic during the seventh century (31) and in a German sample of a central European Neolithic culture (13), whereas this haplogroup is very rare in these places nowadays (32).…”
Section: Resultsmentioning
confidence: 99%
“…Improvements in molecular biological technologies in the last decade have helped overcome some of the limitations that restricted DNA analysis to mitochondrial DNA, which is abundant in mammalian cells. In addition, improvements in forensic genetics (e.g., inhibitor-free DNA extraction, multiplex PCR, short STR amplicons and qPCR) have enabled archaeologists to test nuclear DNA, including Y-chromosome STR typing [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Currently available techniques for DNA analysis using "forensic" procedures [11] can be combined with the classical anthropological examination, advanced imaging and CT scanning techniques [12] and isotope analysis [13] to improve the quality of information that is retrieved from ancient artifacts. A multidisciplinary approach to examining ancient human remains can help verify the DNA analysis results and interpret the findings more precisely.…”
Section: Introductionmentioning
confidence: 99%
“…The Y-chromosome haplogroupprediction method used utilizes the finding that the pattern of STR alleles in persons with the same haplogroup is similar (Athey, 2005). This allele frequency approach is not so precise as SNP typing (Karafet 2008) but STR typing not only provides higher robustness for compromised samples but also enables the relatedness of male lineages to be compared (Vanek et al 2009). Another possible DNA-typing technology would be Massive Parallel Sequencing (MPS) (e.g.…”
Section: Dna Researchmentioning
confidence: 99%
“…The samples were then transferred to a 50-mL tube and further chemically cleaned by inversion for 30 seconds in 5% commercial bleach, followed by 2-3 washes in distilled water (molecular biology grade), one thorough wash in 96% ethanol (Vanek et al 2009) and left to air-dry.…”
Section: Cleaningmentioning
confidence: 99%